Bullying (Journal of Parents and Teachers, 2025)
Bullying is a substantial cause of school violence that involves different behaviors.  According to Olweus, the main roles of the students in bullying situations are portrayed in “The Bullying Circle”: the bully/bullies, follower henchmen, the victim and the supporter passive bully or bullies. It is estimated that about 20%-30% of students who suffer from bullying, 3%-10% are in serious trouble. Which is the profile of students that are bullies/victims/follower henchmen? Bullies can incur in physical aggressions, social exclusion, sexual harassment, altogether with verbal aggression and even cyber harassment; a new type of bullying that most of the time get out of the parent’s and teachers’ hands.
Keywords: Behaviour; Personality development; Learning; System of education